Microbial lipases: advances in production, purification, biochemical characterization, and multifaceted applications in industry and medicine - Ahmed A. Abdelaziz; Amal M. Abo-Kamar; Esraa Sobhy Elkotb; Lamiaa A. Al-Madboly (Microbial Cell Factories)
Abstract Lipases are biocatalysts of significant industrial and medical relevance, owing to their ability to hydrolyze lipid substrates and catalyze esterification reactions under mild conditions. This review provides a comprehensive overview of microbial lipases’ production, purification, and biochemical properties. It explores optimized fermentation strategies to enhance enzyme yield, including using agro-industrial residues as substrates. The challenges associated with purification techniques such as ultrafiltration, chromatography, and precipitation are discussed, alongside methods to improve enzyme stability and specificity. Additionally, the review addresses the growing importance of genetic engineering approaches for improving lipase characteristics, such as activity, stability, and specificity. Additionally, this review highlights the diverse applications of microbial lipases in industries, including food, pharmaceuticals, biofuels, and cosmetics. The enzyme’s role in bioremediation, biodegradation, and the synthesis of bioactive compounds is analyzed, emphasizing its potential in sustainable and eco-friendly technologies. The biocatalytic properties of lipases make them ideal candidates for the green chemistry initiatives in these industries. In the biomedical domain, lipase has shown promise in drug delivery systems, anti-obesity treatments, and diagnostics. This review provides insights into the strategic development of microbes as microbial cell factories for the sustainable production of lipases, paving the way for future research and industrial innovations in enzyme technology.